The Influence of Transformational Leadership Style on Employee Psychological Empowerment: Literature Review - Faizah Oktaviani (Kirana Publisher (KNPub), 2026)
The effectiveness of a company's performance is determined by the quality of human resources. In this modern era, technological advancements and company competition are getting tougher. Good quality human resources can be a stimulus for companies to compete with other companies. Thus, there is a need for psychological empowerment of employees so that they are motivated so that they can work as effectively as possible. In implementing employee psychological empowerment, leadership style is very influential. Companies can explore the potential of each employee by applying a transformational leadership model. Therefore, this study aims to describe the effect of transformational leadership style on increasing employee psychological empowerment in working in the company. Furthermore, in the process of data acquisition, this study uses a qualitative method through a literature review approach. The reference sources for this research consist of various journals obtained using the Google Scholar feature. The results of this study indicate that one of the factors that have a positive effect on increasing employee psychological empowerment is the transformational leadership model. So in this case it shows that the more optimal the transformational leadership provided by the company leader, the more optimal the psychological empowerment of employees.